Intervensi China Terhadap Pembukaan Kantor Perwakilan Diplomatik Taiwan Di Negara Lain - Pattiwaellapia, Vigor; Peilouw, Johanis Steny Franco; Waas, Richard Marsilio (Faculty of Law, Universitas Pattimura, 2024)
Introduction: According to the Montevideo Convention, States must have a government, have defined territories, have diplomatic relations with other countries, and have a permanent population.Purposes of the Research: The purpose of this research was to find out the arrangements for opening a diplomatic representative office in a country and how China's intervention in opening a representative diplomatic office is in accordance with diplomatic law, that Taiwan has a unique position in being to friendly internasional law. Demestically Taiwan has Methods of the Research: The research method used is normative legal research method. The problem approach used is the statutory approach, the conceptual approach. The legal materials used are primary legal materials and secondary legal materials. Procedures and Collection of Legal Materials using the method of inventorying laws and regulations and Processing and Analysis of legal materials using data analysis techniques with deductive logic.Results of the Research: Based on the results of the research, it can be concluded that Taiwan has a unique position in being friendly to international law. Domestically Taiwan has all the qualities of a “formal state” including citizenship, jurisdiction, territoriality, government, and sovereignty. Taiwan is sovereign according to the definition of international law Taiwan is the highest power that is independent from any power in running its government, but Taiwan does not have equal recognition internationally.